Mindfulness Pocketbook : Little exercises for a calmer life - Hasson, Gill (Chichester, West Sussex : Capstone, a Wiley brand, 2020)
"With over 100,000 copies sold, bestselling author Gill Hasson is back! Experts increasingly recognise that developing mindfulness skills is an effective way to improve performance, reduce stress, enhance emotional intelligence, increase life satisfaction, and develop leadership skills. A mindful person consciously brings awareness to the here--and--now with openness, interest, and receptiveness. Mindfulness Pocketbook 2nd Edition is the take--with--you guide to receptive, constructive thinking. Being mindful opens you up to new ideas and fresh ways of doing things, reducing stress and increasing your enjoyment in life. This new revised edition of Gill Hasson's bestselling Mindfulness Pocketbook is packed with even more exercises, practices, and reflective tools to develop balance and harmony in all areas of life. New material for this edition will focus on mindfulness for enjoyment, including: Being mindful outside, enjoying nature Using mindful techniques to unleash creativity Mindful physical activity for a healthy body and mind Mindfulness at work Mindfulness Pocketbook 2nd Edition is packed with even more exercises, practices, and reflective tools to develop balance and harmony in all areas of life, with new areas covered such as enjoying nature, mindfulness at work, physical activity and creativity"--
Chapter 57 Singing Your Heart Out -- Chapter 58 Performing Spontaneous Acts of Kindness -- Chapter 59 Focusing and Engaging Your Attention -- Chapter 60 Managing Change -- Chapter 61 Knowing When to Start Over -- Conclusion -- More Mindful Quotes and Sayings -- About the Author -- Also by Gill Hasson -- EULA
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Description based on online resource; title from digital title page (viewed on August 19, 2020).
WorldCat record variable field(s) change: 650
Keywords: Stress management; Mind and body; Stress (Psychology); Stress (Physiology); Stress, Psychological; Mindfulness; Stress, Physiological; Electronic books